Catalytic efficiency of oxidizing honeycomb catalysts integrated in firewood stoves evaluated by a novel measuring methodology under real-life operating conditions. (March 2018) - Reichert, G.; Schmidl, C.; Haslinger, W.; Stressler, H.; Sturmlechner, R.; Schwabl, M.; Wöhler, M.; Hochenauer, C.
Abstract: Catalytic systems integrated in firewood stoves represent a potential secondary measure for emission reduction. However, the evaluation of catalytic efficiency is challenging since measurements, especially for PM emissions, upstream an integrated catalyst are not possible. Therefore, a special test facility, called "DemoCat", was constructed which enabled parallel measurements in catalytically treated and untreated flue gas. The catalytic efficiency for CO, OGC and PM emissions was investigated under real-life operating conditions including ignition and preheating. The results confirmed a significant emission reduction potential (CO: > 95%, OGC: > 60%, PM: ∼30%). The conversion rates of CO and OGC emissions correlated with the space velocity and the coated area of honeycomb carriers which represent key parameters for the integration design. A quick response of the catalytic effect of around 5–12 min after ignition was observed when reaching 250 °C flue gas temperature at the catalyst. Most effective CO and OGC emission conversion was evident during the start-up and burn-out phase of a firewood batch. This reveals an important synergy for primary optimization which focuses particularly on the stretched intermediate phase of a combustion batch. The catalytic effect on PM emissions, especially on chemical composition, needs further investigations. Highlights: Novel methodology evaluating the catalytic efficiency under real-life conditions. Quick response of catalyst activity by integrated application observed. Effect of honeycomb structure on catalytic efficiency. Space velocity and coated area as key parameters for integration design. Synergy between integrated catalysts and primary measures for emission reduction.